2007
DOI: 10.1111/j.1365-2729.2006.00212.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Sorting the wheat from the chaff’: investigating overload in educational discussion systems

Abstract: This paper reports on research to investigate design features of asynchronous discussion systems for higher education. The research aims to identify features that increase the benefits of discussion systems and reduce the problems. The paper focuses on a major theme that emerged from interviews with learners and teachers: information overload. Interview findings, together with literature and system reviews, were used to identify four areas of possible system enhancement aimed at alleviating overload: branched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 32 publications
(29 reference statements)
0
15
0
Order By: Relevance
“…Second, previous studies also suggest that students stop contributing if they perceive that other students pontificate in the online discussion (e.g., giving their opinions about something as though they know everything about it), or if they feel threatened by other students or if the tone of the discussion becomes too emotional (Hewitt 2005), or rude (Murphy and Coleman 2004). Not seeing the need for online discussion Dennen (2005), Fung (2004), Zhao and McDougall (2005), Oliver and Shaw (2003) and Xie et al (2006) Behavior of instructor or other participants (e.g., tone of postings-threatening, pontification on the part of others, lack of peer response, lack of instructor response) Bodzin and Park (2000), Hew and Cheung (2003b, c), Hew et al (2005), Hewitt and Teplovs (1999), Hewitt (2005), Jeong (2004), Oliver and Shaw (2003), Xie et al (2006), Zhao and McDougall (2005) and Zhu (2006) Personality traits (e.g., low degrees of curiosity, extraversion, agreeableness, openness) Chen and Caropreso (2004), Khan (2005) and Oliver and Shaw (2003) Difficulty in keeping up with the discussion Cheung and Hew (2006), Jones et al (2004) and Kear (2001) Not knowing what to contribute Fung (2004), Hewitt (2005) and Khan (2005) Exhibiting surface level thinking or lowlevel knowledge construction Khine et al (2003) Technical aspects (e.g., usability issues) Hummel et al (2005b) and Murphy and Coleman (2004) Third, students may cease to contribute if the instructor does not show interest or involvement, such as giving encouragement or feedback. Xie et al (2006), for example, reported that students decreased their motivation level to contribute if they perceived less involvement of their instructor in the online discussi...…”
Section: Behavior Of Other Participantsmentioning
confidence: 97%
See 2 more Smart Citations
“…Second, previous studies also suggest that students stop contributing if they perceive that other students pontificate in the online discussion (e.g., giving their opinions about something as though they know everything about it), or if they feel threatened by other students or if the tone of the discussion becomes too emotional (Hewitt 2005), or rude (Murphy and Coleman 2004). Not seeing the need for online discussion Dennen (2005), Fung (2004), Zhao and McDougall (2005), Oliver and Shaw (2003) and Xie et al (2006) Behavior of instructor or other participants (e.g., tone of postings-threatening, pontification on the part of others, lack of peer response, lack of instructor response) Bodzin and Park (2000), Hew and Cheung (2003b, c), Hew et al (2005), Hewitt and Teplovs (1999), Hewitt (2005), Jeong (2004), Oliver and Shaw (2003), Xie et al (2006), Zhao and McDougall (2005) and Zhu (2006) Personality traits (e.g., low degrees of curiosity, extraversion, agreeableness, openness) Chen and Caropreso (2004), Khan (2005) and Oliver and Shaw (2003) Difficulty in keeping up with the discussion Cheung and Hew (2006), Jones et al (2004) and Kear (2001) Not knowing what to contribute Fung (2004), Hewitt (2005) and Khan (2005) Exhibiting surface level thinking or lowlevel knowledge construction Khine et al (2003) Technical aspects (e.g., usability issues) Hummel et al (2005b) and Murphy and Coleman (2004) Third, students may cease to contribute if the instructor does not show interest or involvement, such as giving encouragement or feedback. Xie et al (2006), for example, reported that students decreased their motivation level to contribute if they perceived less involvement of their instructor in the online discussi...…”
Section: Behavior Of Other Participantsmentioning
confidence: 97%
“…Moreover, students may exhibit surface level critical thinking in their contribution (Khine et al 2003). For example, Hew and Cheung (2003b) found that most of the surface level thinking was due to the fact that students lack critical thinking skills such as making conclusions or judgments without offering any justification; propose solutions with little details or explanations; and stating that one shares the conclusions or judgments made by others without taking these further.…”
Section: Student Personality Traitsmentioning
confidence: 97%
See 1 more Smart Citation
“…While much of the online or blended delivery of courses in higher education is didactic in nature, the distinctive asynchronous platform can be used to promote peer learning (Harris & Sandor, 2007;Kear & Heap, 2007).…”
Section: Learner Participation In Online Discussionmentioning
confidence: 99%
“…CMC uses telecommunication technologies such as email, real-time chat, computer conferencing/online discussion systems, and online databases to support human communication between spatially separated learners (Jonassen et al 1995). Although CMC can support teaching and learning by making information and communication easily accessible via computer networks, one of the main problems caused by the medium is information overload (IO) (Burge 1994;Eastmond 1995;Harasim 1987;Kear and Heap, 2007;Paulo 1999;Vonderwell and Zachariah 2005). IO becomes a problem when students simultaneously face having to acquire the technical skills necessary to participate in CMC and manage a large volume of information both on the course website and through computer conferencing (Harasim 1987).…”
mentioning
confidence: 99%